A smart socks system for running gait analysis - Eizentals, P.; Katashev, A.; Oks, A. (Proceedings of the 7th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2019)
Running gait analysis is an often used tool for running performance improvement and injury prevention due to an incorrect running style. The typical gait analysis methods are unavailable to amateur runners outside of special clinics due to their relatively high cost. Smart socks are a relatively cheap gait analysis method that can be used by amateur runners and professional athletes for running performance improvement. This paper presents a smart socks system for feet plantar pressure measurement during running, as well as methods for characterisation of the acquired plantar pressure measurement for running gait analysis. The validation of the smart socks with a Pedar insole system is described, and the measurement analysis methods are demonstrated by practical running tests. The validation tests demonstrated good temporal and pressure sensing characteristics of the system, while the simplicity of the developed gait analysis methods was demonstrated in the practical tests.